Whole-flint corn grain or tropical grass hay free choice in the diet of dairy calves - Toledo, A. F.; da Silva, A. P.; Poczynek, M.; Coelho, M. G.; Silva, M. D.; Polizel, D. M.; Reis, M. E.; Virgínio, G. F.; Millen, D. D. [UNESP]; Bittar, C. M.M. (American Dairy Science Association, 2020)
Tropical grass hay feeding is related to improved ruminal health; however, it may decrease energy intake. On the other hand, whole-flint corn grain may be an alternative fiber source in the diet of dairy calves. Forty-two Holstein calves were used in a randomized block design, considering sex, birth date, and weight at 21 d of age, when the supply of whole-flint corn grain or tropical grass hay started. Three component-fed solid diets were compared: (1) starter concentrate only during the preweaning and starter concentrate with free choice of chopped Tifton-85 hay postweaning (SC), (2) starter concentrate with free choice of chopped Tifton-85 hay pre- and postweaning (SCH), and (3) starter concentrate with free choice of whole-flint corn grain pre- and postweaning (SCW). The animals were evaluated from 21 to 84 d of age. Calves were managed equally during the first 21 d, fed with 6 L/d of whole milk and a commercial starter concentrate (46% nonfiber carbohydrates, small particles, and pelleted) ad libitum. After that, milk feeding was reduced to 4 L/d until gradual weaning at 56 d of age. At 56 d of age, 4 animals per treatment were randomly chosen to be slaughtered for digestive tract weight evaluation and to collect tissue for histological analysis of the ruminal wall, duodenum, and cecum, whereas the other 30 animals were weaned and evaluated for a further 22 d when the SC diet also received hay ad libitum. Feed intake was measured daily. Weight gain and metabolic indicators of intermediate metabolism were evaluated weekly. Ruminal fluid was collected at wk 6, 8, 10, and 12 of age. The SCH diet increased the total and starter dry matter intake, and consequently, the average daily gain and body weight at 56 d of age. The SCW diet promoted an increase in propionate and decreased acetate-to-propionate ratio. Morphometric variables were affected by the SCH diet. The postweaning performance was unaffected by solid diets; however, the SCW diet decreased ruminal and fecal pH. Feeding hay, starting at 21 d of age, can stimulate early solid diet intake, promoting better performance and ruminal and intestinal development, when a highly fermentable and small particle pelleted starter is fed.
Keywords: papillae; pH; postweaning; villus